From urbanization to ruralization - Ari Sulistyorini (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2020)
Urbanization is a serious problem for Indonesia. Jakarta is the epicenter of urbanization, which is the center of wealth, which sucks in the migration of people from villages that creates population density, social inequality, as well as congestion and flooding. President Joko Widodo seeks to stem urbanization as part of an Indonesia centric platform, while Minister of Finance Sri Mulyani seeks to spur urbanization for economic growth. This article aims to express criticism of urbanism, as well as offering ruralization, which moves back to rural, with agriculture as the backbone, as well as districts, villages, farmers, fishermen, and farmers as the main actors. This article does not work with geography, demography, or economics, but with political science, which uses interpretive methods and critical analysis. With this analysis, this study of ideas critically finds that urbanization has created Indonesia as an economically, socially, and politically complex urban society. This urbanization has given the wealth and splendor of the city but also presents a serious paradox: city decay (explosion into / implosion), and rural impoverishment (explosion out / explosion). A city-centric solution with a sustainable city recipe will only deal with urban decay but ignore rural impoverishment. The Indonesia-centric solution with rural and rural areas, with local emancipation, is a better answer for equality, justice, and prosperity. Jepara, the most prosperous district in Central Java, is an example of ruralization that goes beyond the project approach from above.